Transitioning from Oxime to the Next Potential Organophosphorus Poisoning Therapy Using Enzymes - Rauda A. Mohamed; Keat K. Ong; Noor Azilah M. Kasim; Norhana A. Halim; Siti Aminah M. Noor; Victor F. Knight; Nurul Najwa Ab. Rahman; Wan Md Zin W. Yunus (Journal of Chemistry)
For years, organophosphorus poisoning has been a major concern of health problems throughout the world. An estimated 200,000 acute pesticide poisoning deaths occur each year, many in developing countries. Apart from the agricultural pesticide poisoning, terrorists have used these organophosphorus compounds to attack civilian populations in some countries. Recent misuses of sarin in the Syrian conflict had been reported in 2018. Since the 1950s, the therapy to overcome this health problem is to utilize a reactivator to reactivate the inhibited acetylcholinesterase by these organophosphorus compounds. However, many questions remain unanswered regarding the efficacy and toxicity of this reactivator. Pralidoxime, MMB-4, TMB-4, obidoxime, and HI-6 are the examples of the established oximes, yet they are of insufficient effectiveness in some poisonings and only a limited spectrum of the different nerve agents and pesticides are being covered. Alternatively, an option in the treatment of organophosphorus poisoning that has been explored is through the use of enzyme therapy. Organophosphorus hydrolases are a group of enzymes that look promising for detoxifying organophosphorus compounds and have recently gained much interest. These enzymes have demonstrated remarkable protective and antidotal value against some different organophosphorus compounds in vivo in animal models. Apart from that, enzyme treatments have also been applied for decontamination purposes. In this review, the restrictions and obstacles in the therapeutic development of oximes, along with the new strategies to overcome the problems, are discussed. The emerging interest in enzyme treatment with its advantages and disadvantages is described as well.